Several Important In Vitro Improvements in the Amplification, Differentiation and Tracing of Fetal Liver Stem/Progenitor Cells - Liu, Wei-hui; Liu, Zheng-cai; You, Nan; Zhang, Ning; Wang, Tao; Gong, Zhen-bin; Liu, Hong-bao; Dou, Ke-feng (PLOS ONE, 2012)
Objective We previously isolated fetal liver stem/progenitor cells (FLSPCs), but there is an urgent need to properly amplify FLSPCs, effectively induce FLSPCs differentiation, and steadily trace FLSPCs for in vivo therapeutic investigation. Methods FLSPCs were maintained in vitro as adherent culture or soft agar culture for large-scale amplification. To direct the differentiation of FLSPCs into hepatocytes, FLSPCs were randomly divided into four groups: control, 1% DMSO-treated, 20 ng/ml HGF-treated and 1% DMSO+20 ng/ml HGF-treated. To trace FLSPCs, the GFP gene was introduced into FLSPCs by liposome-mediated transfection. Results For amplifying FLSPCs, the soft agar culture were more suitable than the adherent culture, because the soft agar culture obtained more homogeneous cells. These cells were with high nuclear:cytoplasmic ratio, few cell organelles, high expression of CD90.1 and CD49f, and strong alkaline phosphatase staining. For inducing FLSPCs differentiation, treatment with HGF+DMSO was most effective (P<0.05), which was strongly supported by the typical morphological change and the significant decrease of OV-6 positive cells (P<0.01). In addition, the time of indocyanine green elimination, the percentage of glycogen synthetic cells, and the expressions of ALB, G-6-P, CK-8, CK-18 and CYP450-3A1 in HGF+DMSO-treated group were higher than in any other group. For tracing FLSPCs, after the selection of stable FLSPC transfectants, GFP expression continued over successive generations. Conclusions FLSPCs can properly self-renew in soft agar culture and effectively differentiate into hepatocyte-like cells by HGF+DMSO induction, and they can be reliably traced by GFP expression.